Exploring The Psychological State of Career Well-Being in Vocational Students' Choice of Major Interest - Rafli, Muhammad; Usrah, Muzayyinah Al (IAIN Kudus, 2024)
Exploring the psychological state of career well-being in vocational students' choice of major interest. This research aims to explore the level of career satisfaction through interest in the scientific fields of majors taken by Vocational High School students in South Sulawesi, especially at SMK Negeri 1 Bantaeng. This research uses a descriptive quantitative approach. This research uses the Career Well-being Scale (CWS) instrument consisting of 14 items which have been tested for Confirmatory Factor Analysis (CFA). The sample for this research was 200 students at SMK Negeri 1 Bantaeng. Descriptive data analysis techniques using the JASP statistical test application. The research findings through aspects of positive affective career planning conditions, career meaningfulness conditions, career network conditions/social support as a whole are categorized as high. Recommendations for further research are needed to look at factors and further interventions related to career development in schools.Keywords: Career Psychological Wellbeing; Interest; Vocational school students.